Nilai Kearifan Lokal pada Legenda Ki Buyut Batisari Kecamatan Pabedilan - Lestari, Thita Siti; Mulyaningsih, Indrya; Khuzaemah, Emah (Kajian Bahasa dan Sastra (KABASTRA), 2023)
This study aims to describe: (1) the value of local wisdom in the legend of Ki Buyut Batisari, Pabedilan District by the local community, (2) its use as a drama learning module in grade VIII junior high school. This type of research is a qualitative research with descriptive method. The data from this study is the legend of Ki Buyut Batisari. Data collection techniques indirectly affect the acquisition of research data, therefore data collection techniques must be adapted to the research objectives. In this study, in obtaining data, the authors used data techniques in the form of: (1) Listening techniques, (2) Recording techniques. The results of this study can be concluded that the value of local wisdom in the legend describes research data related to the problem that has been formulated, namely the value of wisdom in the legend of Ki Buyut Batisari, Pabedilan District, Cirebon Regency in the form of: (1) mutual cooperation, (2) honesty, (3) Commitment, (4) Confidence, (5) Politeness, (6) Authority, (7) Honesty. Using it as a module contains KD 3.16 Examining the structure and language of local dramas that are read and heard, KD 4.16 Acting out the contents of local regional dramas that are read and heard. The implications of the value of local wisdom in the legend of Ki Buyut Batisari, Pabedilan Sub-District, can make it easier for teachers to explain cultural values ​​that can be used as lessons and students and generations will always preserve their local culture, especially local wisdom in the legend of Ki Buyut Batisari.